Crime fiction and the translation of collective violence into French in Un lugar llamado Oreja de Perro - Sandoval, Diego Vilchez (2024)
In this paper, we reflect on the translation of the novel Un lugar llamado Oreja de Perro by Iván Thays into French, and its discourse on collective violence against the rural population in Peru after the non-international armed conflict (CAI) (1980–2001). This novel shows features of crime fiction: a story founded on brief order disruption, violence built through victim-perpetrator binarity, and inspiration from a representative historical, political, and cultural period. Peruvian literature about the CAI has been introduced into international markets through translation, but translation studies have paid little attention to it. A contrastive analysis allowed to observe the features of crime fiction within the novel and the effects of its translation upon the discourse on violence. The translation of the novel attempts to preserve the features of the genre prioritizing the delivery of a discourse on violence to the detriment of the cultural features which build violence within the novel; in this case, the ethnic-cultural dimension of the conflict, when these elements are incommensurable between both cultures. Thus, the French translation tends toward domestication but shows foreignizing exceptions.